Public Health Perspectives of Genetically Modified Food: A Comprehensive Review: Public Health Perspectives of Genetically Modified Food - Asif Ilyas, Muhammad; Ali, Mansoor; Aslam, Maryum; Hassan, Ayesha; Muqaddas, Rehmana; Akhtar, Naheed; Zahid Aslam, Muhammad; Ketema, Sisay; Fiza Nayab, Syeda; Arshad Maan, Naeem; Razaq, Zarafshan; ullah, Ikram (Pakistan Journal of Health Sciences, 2022)
Now a day food fortification using genetically modified organism was highly popular, secured and affordable for the current food demanded population. Many commendable uses of microbes were found in genetically modified Food. This review paper attempted to address the impact of microorganisms employed in genetically modified food. PubMed, Science Direct, Google Scholar, and other search engines were used to collect papers. The impact of microorganisms in Food Productions was briefly explored and illustrated in the table and figures. Climate resilience, high yield, environmental adaptability, and high protein, 40–50% and 20–40% produced by bacteria and alga respectively, were only a few advantages of foods that have been genetically modified foods with microbes. Additionally, it improves human health by reducing poverty, ensuring food security, and preventing disease. Therefore, genetically modified foods brought a positive impact for human health.